(untitled) (Revista Brasileira Multidisciplinar, 2026)
This article analyzes the application of the dual criminal liability (double imputation) mechanism to individual enterprises and their respective owners (natural persons) in the context of environmental crimes. It begins with Law No. 14,195/2021, which repealed the Empresa Individual de Responsabilidade Limitada (EIRELI) and automatically converted it into the Sociedade Limitada Unipessoal (SLU), to discuss the appropriateness of holding both entities simultaneously criminally liable. The central question is: is it legally and ethically justifiable to apply dual penalties—to the legal entity and to the natural person—when both are essentially one and the same? To address this issue, the study examines Article 3 of Law No. 9,605/1998, the constitutional foundations of corporate criminal liability established by the 1988 Federal Constitution, and the theories of legal fiction and juridical reality concerning the nature of collective persons, as well as the current regulation of single-member limited companies. Methodologically, this study adopts a qualitative, theoretical-exploratory, and deductive approach, based on bibliographic and documentary research (legislation, doctrine, and case law), combined with normative and principled analysis—including proportionality, reasonableness, ne bis in idem, the social function of the company, and business preservation. The article concludes by proposing interpretative and legislative adjustments to harmonize environmental criminal protection with the safeguarding of small-scale business structures.